Health Promotion through Audiovisual Media on Improving Students' Knowledge, Attitudes, and Behavior about Mental Health : Promosi Kesehatan melalui Media Audiovisual terhadap Peningkatan Pengetahuan, Sikap, dan Perilaku Siswa tentang KesehatanMental - Sadya Bustomi; Prihayati; Ismarina; Diah Nurul Qulbi; Rizka Fitriani; Binawan Septiadi (KHD Production, 2025)
Mental disorders are becoming increasingly prevalent across all age groups, particularly among adolescents. Given that adolescence is a transitional phase between childhood and adulthood, this activity was implemented due to the low level of understanding among adolescents regarding mental health issues and the persistent stigma associated with psychological problems. This community service activity aims to improve students' knowledge, attitudes, and behaviors related to mental health through audiovisual media-based health promotion. The implementation method includes preparation, intervention, and evaluation. The intervention involved screening educational videos on mental health topics, followed by interactive discussions and group reflections. Evaluation was conducted by comparing pre-test and post-test results. The results showed a significant improvement in students' knowledge, attitudes, and behaviors after the intervention. Students became more open and understood the importance of maintaining mental health, and were more willing to seek help if experiencing psychological distress. This activity received a positive response from both the school and students. Audiovisual media has proven effective as an educational tool for adolescents. Going forward, it is hoped that this program can be continued and incorporated into ongoing character development for students at school.